Implementasi Metode Waypoint pada Sistem Navigasi Automated Guided Vehicle (AGV) - Arsy Ananta, Mohammad; Amperawan, Amperawan; Anisah, Masayu (Journal of Comprehensive Science, 2024)
In the manufacturing and logistics industry, operational efficiency is key to increasing productivity and reducing operational costs. One technological innovation that plays an important role is the use of Automated Guided Vehicles (AGVs) equipped with GPS-based navigation systems. This research aims to implement a GPS navigation system on AGVs using the waypoint method with a focus on improving movement accuracy and vehicle route optimisation. The waypoint method is used to determine the coordinate points of the destination that must be reached by the AGV. Tests were conducted on several movement scenarios, which included setting waypoints on the trajectory. The test results show that the developed navigation system is able to reduce distance deviation and improve the consistency of AGV movement towards predetermined waypoints. In the first test, the AGV successfully reduced the deviation from 9 metres to 3 metres, demonstrating the system's ability to gradually adjust the position. The second and third tests also showed significant deviation reduction, reinforcing the reliability of this method in varied environments. The conclusion of this research is that the integration of GPS technology with the waypoint method is effective in improving AGV performance for applications in the manufacturing and logistics industries.